DETERMINAN PERILAKU BIDAN DALAM PENCEGAHAN INFEKSI HIV AIDS PADA PERTOLONGAN PERSALINAN DI KABUPATEN BANYUMAS - Purwanti, Sugi; Fajarsari, Dyah; Handayani, Rohmi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
An increasing number of insiden with HIV/AIDS has beeing very real, Indonesia ranks third among the countries experiencing the most rapid increase of cases of HIV/AIDS. Health workers relating to HIV/AIDS, especially midwives who helping mothers give a birth with HIV / AIDS infections. Precaution transmission of HIV-AIDS infection during the process of delivery is required by universal pre caution, one of them is self-protection equipment. The objective of research was knowing the factors of  knowledge, attitudes, perceptions supervision, the availability of resources related to midwife’s infection prevention behavior of HIV/AIDS in Banyumas district. This research method was an analytic observational studied with cross sectional approach. The population was all midwives worked in the region of 39 public health centers Banyumas. Determination of the number of samples in random clusters of 87 midwives. Analysis of the data used univariate analysis to describe the frequency distribution of each variable, bivariate analysis used chi square test to determine the relationship of each variable. Research results are most midwives have a good knowledge of 51 (59.3%), midwives have a good attitude 48 (55.8%), presence of infection prevention facilities in health centers 57 (66.3%), midwives have a good perception of supervision 45 (52.3%), good infection prevention behavior 58 (67.4%). Uncorrelation between the variables of knowledge, attitude,  presence of infection prevention facilities, perception supervision to infection prevention behaviors. Each p value for each bivariate are 0513, 0771, 0830, 0279. Conclusion of the study are uncorrelation between the variables of knowledge, attitude,  presence of infection prevention facilities, perception supervision to infection prevention behaviors. Keywords: infection prevention behaviors, knowledge, attitude, infection prevention facilities, perception supervision